(3QSGdI eaQOI aj HjGf MLjI GdTgQI hLhGR GdGYJeGO YdjgG aj GKHGJ GdCMcGe GdTQYjIs - (3GdWHGWHGFj, GdcGXej, GdMGFQj, GdCUHgGfj, Ydj Hf eMeO Ydj Hf CHj GdeYGdj, J (B1231 (3gs ((3MSf Hf eMeO HGbQ GdMSjfjs)
(3ChdgG (B:s
(3GdMeO ddg (B...(3gPg QSGdI eaQOI aj HjGf MLjI GdTgQI hLhGR GdGYJeGO YdjgG aj GKHGJ GdGMcGe GdTQYjI bO cJHJgG aj ZGjI GdGSJYLGd eY cKQI GdGTJZGd hHdHGd GdHGd hGNJdGd GdedGd aCbhd (B...s
(3BNQgG (B:s
... (3eTJQc Hjf NUhUjGJ dGHO ef GYJHGQgG MJi jfaY Pdc GdELeGdj hjJYjf Pdc GdeTJQc HUjQhQJg Mce GdTQY HGdfSHI Edi CaYGdgG GfJgi cdGeg Sdeg Gddg hajg JCjjO deG PcQfG (B... (3gPG BNQ eG GfJgis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B5\ 17s
(3GdPQjYI (B6\1479s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs